A silent transformation of keratocystic odontogenic tumour to squamous cell carcinoma: A case report and review of literature - Upendra Gurugubelli; Ramesh Tatapudi; Ravikanth Manyam; Priyankesh Sinha (Wolters Kluwer Medknow Publications, 2016)
Till date cases reported elsewhere in the world regarding keratocystic odontogenic tumor transformation to squamous cell carcinoma are very sparse. It has been usually noticed in adult males, with the predominant location being posterior mandibular area. We hereby report a case of squamous cell carcinoma involving anterior mandibular area to posterior mandibular region in a 65-year-old female patient with no evidence of any ulceration and growth intraorally, suggesting that the tumor had a bony origin. Therefore, thorough monitoring of such tumours is necessary to arrive at a proper diagnosis, followed by providing treatment at the earliest.